Functional imaging in the zebrafish retinotectal system using RGECO - Walker, Alison S.; Burrone, Juan; Meyer, Martin P. (Frontiers in Neural Circuits, 2013)
Genetically encoded calcium indicators (GECIs) allow repeated, non-invasive measurements of neural activity in defined populations of neurons, but until recently GECIs based on single fluorescent proteins have been limited to the green region of the colour spectrum. Recent efforts in protein engineering have expanded the colour palette of GECIs. One of these new GECIs, the red RGECO, is spectrally separate from the traditional GFP-based sensors such as GCaMP, and therefore opens the way for simultaneous, multicolour imaging of neural activity. While RGECO has been shown to report spontaneous calcium fluctuations in neurons, the precise relationship of RGECO signal to evoked-neural activity is not known. Measurements of neural activity using RGECO in vivo have also not been reported. Using dissociated hippocampal neurons we performed a systematic analysis of two forms of RGECO- a cytosolic form and a presynaptically localised form generated by fusion of RGECO to the presynaptic protein, synaptophysin (SyRGECO). We find that RGECO and GCaMP3 are comparable in terms of dynamic range, signal-to-noise ratios and kinetics but that RGECO is a more reliable reporter of single action potentials. In terms of performance SyGCaMP3 and SyRGECO are comparable, and both are more sensitive reporters of activity than the cytosolic form of each probe. Using the zebrafish retinotectal system we show that SyRGECO and RGECO are can report neural activity in vivo and that RGECO expression permits detailed structural analysis of neuronal arbours. We have exploited these attributes to provide a morphological and functional description of tectal cells selective for motion along the vertical axis. These results open up the possibility of using zebrafish to functionally image genetically defined pre- and postsynaptic circuit components, separable by colour, which will be a powerful approach to studying neural interactions in the brain.